Surviving sepsis campaign: International guidelines for management of sepsis and septic shock in adults 2021 ‐ endorsement by the Scandinavian society of anaesthesiology and intensive care medicine. Issue 5 (6th March 2022) - Rehn, Marius; Chew, Michelle S.; Olkkola, Klaus T.; Ingi Sigurðsson, Martin; Yli‐Hankala, Arvi; Hylander Møller, Morten
Abstract: The Clinical Practice Committee of the Scandinavian Society of Anaesthesiology and Intensive Care Medicine endorses the clinical practice guideline Surviving sepsis campaign : international guidelines for management of sepsis and septic shock 2021 . The guideline serves as a useful bedside decision aid for clinicians managing adults with suspected and confirmed septic shock and sepsis‐associated organ dysfunction.